2020
DOI: 10.1097/corr.0000000000001491
|View full text |Cite
|
Sign up to set email alerts
|

How Are Indeterminate Pulmonary Nodules at Diagnosis Associated with Survival in Patients with High-Grade Osteosarcoma?

Abstract: Background Pulmonary metastases are a poor prognostic factor in patients with osteosarcoma; however, the clinical significance of subcentimeter lung nodules and whether they represent a tumor is not fully known. Because the clinician is faced with decisions regarding biopsy, resection, or observation of lung nodules and the potential impact they have on decisions about resection of the primary tumor, this remains an area of uncertainty in patient treatment. Surgical management of the primary tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 25 publications
1
16
1
Order By: Relevance
“…First, as was noted by Raciborska et al, the presence of multiple bilateral IPN greater than 3 mm in diameter is suggestive of malignancy. Second, as opposed to findings in our prior study on osteosarcoma, 18 metastatic disease is just as likely to develop in extra-pulmonary as in pulmonary sites. Finally, also in contrast to findings in osteosarcoma where IPN growth following neoadjuvant chemotherapy is a poor prognostic factor, this study suggests that in Ewing sarcoma, IPN improvement on chemotherapy reflects a malignant nodule.…”
Section: Table 3acontrasting
confidence: 95%
See 2 more Smart Citations
“…First, as was noted by Raciborska et al, the presence of multiple bilateral IPN greater than 3 mm in diameter is suggestive of malignancy. Second, as opposed to findings in our prior study on osteosarcoma, 18 metastatic disease is just as likely to develop in extra-pulmonary as in pulmonary sites. Finally, also in contrast to findings in osteosarcoma where IPN growth following neoadjuvant chemotherapy is a poor prognostic factor, this study suggests that in Ewing sarcoma, IPN improvement on chemotherapy reflects a malignant nodule.…”
Section: Table 3acontrasting
confidence: 95%
“…17 This approach was utilized during our previous study on osteosarcoma. 18 First, thin (1 mm) and thick (5 mm) slices in the lung window were screened to identify suspicious nodules. Second, if the nodule was absent on the maximum intensity projection (MIP), it was removed from consideration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have reported improved outcomes in patients with osteosarcoma with a lower number of resectable pulmonary metastases 5,20 . However, Kim et al 21 observed that patients with IPNs at the time of diagnosis had poorer survival rates than those without chest CT abnormalities. We categorized patients into two groups based on age (<18 years and ≥18 years) and observed no significant differences in survival rates of adults without nodules and with IPNs.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the latest study showed that around 14% osteosarcoma patients were with lung metastasis at diagnosis and the indeterminate nodules in lung can turn into the metastatic disease at a median time of 5.3 months [7]. Lung metastasis has become the focus in osteosarcoma in recent years.…”
Section: Introductionmentioning
confidence: 98%